Evaluation of the impact of reliance on the regulatory performance in the South African Health Products Regulatory Authority: implications for African regulatory authorities - Danks, Lorraine; Semete-Makokotlela, Boitumelo; Otwombe, Kennedy; Parag, Yashmika; Walker, Stuart; Salek, Sam (Frontiers in Medicine, 2023)
Introduction The World Health Organization (WHO) advocates the use of reliance practices to enable national regulatory authorities (NRAs) to improve patients’ access to medicines. This study considered whether reliance review translates into swifter medicine authorization. Methods Abridged review outcomes were examined for New Chemical Entity (NCE) and generic applications to the South African Health Products Regulatory Authority (SAHPRA) in Chemistry, Manufacturing and Controls (CMC) and clinical/bioequivalence (BE), as well as overall NCE authorization times. Results SAHPRA NCE CMC review time was 91 days (abridged) vs. 179 days (full), applicant response time was 34 vs. 105 days, respectively, and there was a >2-fold time reduction for abridged vs. full CMC review (125 vs. 284 days). There was a 99-day decrease in clinical approval time through an abridged review (230 vs. 329 days) and a decrease in marketing authorization time for NCE abridged assessment (446 vs. 619 days). SAHPRA review time for generic applications was 97 days (abridged) vs. 191 days (full); applicant response time was 26 days (abridged) vs. 81 days (full) and there was a >2-fold time reduction for CMC and BE abridged vs. full review (122 vs. 272 days). Conclusion These results clearly support World Health Organization recommendations for the use of reliance-based regulatory review to expedite the worldwide availability of safe, effective and needed medications.